Gaining Votes in Europe against Europe? How National Contexts Shaped the Results of Eurosceptic Parties in the 2014 European Parliament Elections - Vincenzo Emanuele; Nicola Maggini; Bruno Marino (Journal of Contemporary European Research, 2016)
In the wake of the harshest economic crisis since 1929, in several European countries there has been a rise of Eurosceptic parties that oppose EU integration. The 2014 European Parliament elections were a fundamental turning point for these parties. In this article, after a theoretical discussion on the concept of Euroscepticism, we provide an updated classification of Eurosceptic parties after the 2014 European Parliament elections. We show the cross-country variability of such parties’ results and present two hypotheses aiming at explaining Eurosceptic parties’ results, one related to each country’s economic context and one related to each country’s political-institutional context. Through a comparative approach and the use of quantitative data, we test the two hypotheses by creating two standardised indices of economic and political-institutional contexts. Three important findings are shown: Eurosceptic parties perform better in either rich, creditor countries or in poor countries; Eurosceptic parties perform better in countries with peculiar political-institutional features, such as high levels of party system instability and a more permissive electoral system; finally, and crucially, favourable political-institutional contexts seem to be more important than favourable economic contexts for Eurosceptic parties’ electoral results